Exact controllability of the wave equation with time-dependent and variable coefficients. (February 2019) - Liu, Yu-Xiang
Abstract: This paper deals with boundary exact controllability for the dynamics governed by the wave equation with variable coefficients in time and space, subject to Dirichlet or Neumann boundary controls. The observability inequalities are established by the Riemannian geometry method under some geometric conditions.